Rethinking the connections between campus courses and Field experiences in College and University-based teacher education - Zeichner, Ken (Educação, 2010)
In this paper, I discuss one of the central problems that has plagued college and university-based pre-service teacher education for many years, the disconnect between the campus and school-based components of programs. First, I will draw on my own experiences as a teacher educator and administrator over the last thirty plus years at the University of Wisconsin-Madison and the literature to lay out various dimensions of this issue. Then, utililizing the concept of hybridity and “third space,” I will discuss a variety of current work in programs across the U.S. that offers much promise in deepening the quality of teacher learning in college and university-based teacher education programs and the ability of teacher education graduates to enact desired teaching practices in complex school settings. This work in creating hybrid spaces in teacher education where academic and practitioner knowledge and knowledge that exists in communities come together in new less hierarchical ways in the service of teacher learning represents a paradigm shift in the epistemology of teacher education programs. I argue that this shift toward more democratic and inclusive ways of working with schools and communities is necessary for colleges and universities to fulfill their mission in the education of teachers. Keywords: Education of teachers; Campus and school-based; Programs across.